Maghrebi rivalries over sub-Saharan Africa: Algeria and Tunisia seeking to keep up with Morocco - Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2020)
The Covid-19 pandemic has moved relations with Sub-Saharan Africa further up the Maghreb countries' agenda and consolidated existing trends. Morocco is the Maghreb state with the most sophisticated Sub-Sahara policy. Its motivations include attractive growth markets in Africa, frustration over restricted access to Europe, stalemated integration in the Maghreb and the wish to see the Western Sahara recognised as Moroccan. Morocco's Sub-Sahara policy has heightened tensions with Algeria and awakened ambitions in Tunisia. Algiers, as a significant funder and security actor in the African Union (AU) and 'protector' of the Western Sahara independence movement, is seeking to thwart Rabat's advances. Tunis for its part is trying to follow in Rabat's footsteps, hoping that closer relations with Africa will boost economic growth. The European Union should treat these trends as an opportunity for African integration and triangular EU/Maghreb/Sub-Sahara cooperation. This could counteract Algeria's feeling of growing irrelevance, strengthen Tunisia's economy, put Morocco's hegemonic ambitions in perspective, and thus mitigate the negative dynamics of the rivalry.
Keywords: 320